Predict Stock Prices using Neural Networks with Historical Stock Prices - V. Ramalingam, V.; Sharma, Vaibhav; Pandian, A. (International Journal of Engineering and Technology, 2018)
Stock markets have always intrigued researchers in industry as well as in academia. Some researchers consider stock price movements completely random. Many scholars have attempted to predict stock price using various sources of data available (like historical stock prices, news articles, twitter data, so on), by applying indigenous methods. Predicting stock prices is a regression task, many conventional techniques have been used to predict stock prices. In recent years, the neural network approach has risen to tackle the problem. The neural networks’ approach has been used to predict the stock prices and stock indexes.